2011
DOI: 10.4084/mjhid.2011.053
|View full text |Cite
|
Sign up to set email alerts
|

Acute Promyelocytic Leukemia: An Experience on 95 Greek Patients Treated in the All-Trans-Retinoic Acid Era

Abstract: Acute promyelocytic leukemia (APL) is highly curable with the combination of all-transretinoic acid (ATRA) and anthracycline based chemotherapy, but the percentage of early deaths remains high. In the present study, we report the clinical, immunophenotypic, cytogenetic and molecular characteristics and outcome of APL patients diagnosed and treated in various Hospitals of Greece and Cyprus.We describe the data of ninety-five APL patients who were diagnosed during the last 15 years. Seven (7.4%) newly diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 97 publications
(159 reference statements)
0
4
0
1
Order By: Relevance
“…While a Turkish study reported a high incidence of early induction death at 40%, (20) a high early death rate of 32% was reported in a Brazilian study, (29) and a Greek study found early death rate to be 14.9%. (34) In another series, the early death rate among patients with APL was 21.5%. (35) These population-based studies suggest that the early death rates depicted in clinical trials do not correspond to real-life circumstances and have not changed much in the ATRA era, as seen in our study.…”
Section: Discussionmentioning
confidence: 93%
“…While a Turkish study reported a high incidence of early induction death at 40%, (20) a high early death rate of 32% was reported in a Brazilian study, (29) and a Greek study found early death rate to be 14.9%. (34) In another series, the early death rate among patients with APL was 21.5%. (35) These population-based studies suggest that the early death rates depicted in clinical trials do not correspond to real-life circumstances and have not changed much in the ATRA era, as seen in our study.…”
Section: Discussionmentioning
confidence: 93%
“…ED rates ranging from 9.6% to 61.5%, depending on the population studied. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Efforts to develop international recommendations have led to a gradual improvement in ED rates over the past 3 decades, from 28% in the 1990s to $15% over the past 2 decades. [27][28][29] Major risk factors for ED include advanced age, high-risk disease, poor performance status, and coexisting infection.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some trials have excluded patients from analyses if they die before receiving treatment [6]. On the other hand, in population-based analyses and single-center experiences from different countries, the rate of induction mortality rate is up to 61.5%, which is higher than expected [11][12][13][14]. Especially populationbased reports from the developed countries emphasize neither ED nor OS improved in the past two decades despite modern therapy methods [15][16][17].…”
Section: Introductionmentioning
confidence: 99%